Quality of life (QoL) evaluation of children using cochlear implants: agreement between pediatric and parent proxy-QoL reports. (1st November 2020) - Hendriksma, Martine; Bruijnzeel, Hanneke; Bezdjian, Aren; Kay-Rivest, Emily; Daniel, Sam J.; Topsakal, Vedat
Abstract : Objectives: Cochlear implants are known to significantly improve the quality of life (QoL) of implanted children. However, variability exists between self-reported outcomes and parental-reported QoL questionnaires. We evaluated the QoL agreement between children and their parents following cochlear implantation and determined which factors lead to increased agreement. Methods: A cross-sectional study was performed including pediatric cochlear implant recipients and their parents. We evaluated postoperative QoL using The Pediatric Quality of Life Inventory (PedsQL). To assess agreement between pediatric and parental QoL perception, PedsQL intra-class correlations (ICCs) were calculated. Results: Thirty-five children and their parents completed QoL questionnaires. Children who were evaluated between 8–12 years of age reported highest absolute total and subscale PedsQL scores. Highest agreement was found amongst parents and children when: (1) children were between 8–12 years at QoL assessment (ICC: between 0.917[95%CI: 0.676–0.981] and 0.972[95%CI: 0.882–0.994]), and (2) when evaluating the physical health QoL domain (ICC: 0.964[95%CI: 0.849–0.992]). Conclusions: This study demonstrates high agreement (ICC > 0.8) between pediatric and parental QoL report in children aged between 8–12 years at QoL assessment. Therefore, results confirm that: (1) QoL agreement between pediatric self-report and parent proxy-report is high in chronically ill children and (2) children using cochlear implants can reliably report QoL between 8–12 years.